Metabolic Flow of C6 Volatile Compounds From LOX-HPL Pathway Based on Airflow During the Post-harvest Process of Oolong Tea - Zhou, Zi-wei; Wu, Qing-yang; Ni, Zi-xin; Hu, Qing-cai; Yang, Yun; Zheng, Yu-cheng; Bi, Wan-jun; Deng, Hui-li; Liu, Zhen-zhang; Ye, Nai-xin; Lai, Zhong-xiong; Sun, Yun (Frontiers in Plant Science, 2021)
Aroma is an essential quality indicator of oolong tea, a tea derived from the Camellia sinensis L. plant. Carboxylic 6 (C6) acids and their derivative esters are important components of fatty acid (FA)-derived volatiles in oolong tea. However, the formation and regulation mechanism of C6 acid during postharvest processing of oolong tea remains unclear. To gain better insight into the molecular and biochemical mechanisms of C6 compounds in oolong tea, a combined analysis of alcohol dehydrogenase (ADH) activity, CsADH2 key gene expression, and the FA-derived metabolome during postharvest processing of oolong tea was performed for the first time, complemented by CsHIP (hypoxia-induced protein conserved region) gene expression analysis. Volatile fatty acid derivative (VFAD)-targeted metabolomics analysis using headspace solid-phase microextraction–gas chromatography time-of-flight mass spectrometry (HS-SPEM-GC-TOF-MS) showed that the (Z)-3-hexen-1-ol content increased after each turnover, while the hexanoic acid content showed the opposite trend. The results further showed that both the ADH activity and CsADH gene expression level in oxygen-deficit-turnover tea leaves (ODT) were higher than those of oxygen-turnover tea leaves (OT). The C6-alcohol-derived ester content of OT was significantly higher than that of ODT, while C6-acid-derived ester content showed the opposite trend. Furthermore, the HIP gene family was screened and analyzed, showing that ODT treatment significantly promoted the upregulation of CsHIG4 and CsHIG6 gene expression. These results showed that the formation mechanism of oolong tea aroma quality is mediated by airflow in the lipoxygenase–hydroperoxide lyase (LOX-HPL) pathway, which provided a theoretical reference for future quality control in the postharvest processing of oolong tea.